On the Analysis of Reed Solomon Coding for Resilience to Transient/Permanent Faults in Highly Reliable Memories - Schiano, L.; Ottavi, M.; Lombardi, F.; Pontarelli, S.; Salsano, A. (Design, Automation and Test in Europe, 2005)
Single Event Upsets (SEU) as well as permanent faults can significantly affect the correct on-line operation of digital systems, such as memories and microprocessors; a memory can be made resilient to permanent and transient faults by using modular redundancy and coding. In this paper, different memory systems are compared: these systems utilize simplex and duplex arrangements with a combination of Reed Solomon coding and scrubbing. The memory systems and their operations are analyzed by novel Markov chains to characterize performance for dynamic reconfiguration as well as error detection and correction under the occurrence of permanent and transient faults. For a specific Reed Solomon code, the duplex arrangement allows to efficiently cope with the occurrence of permanent faults, while the use of scrubbing allows to cope with transient faults.